The Relationship Between Human Resource Management, Technology Adaptation, and Principal Leadership on Teacher Productivity - Alghifari, Ahmad Septian; Abidin, Munirul (Al-Qalam Institue, 2025)
This study examines the relationship between human resource management, technology adaptation, and principal leadership in influencing teacher productivity. Recognizing that teachers are central to effective educational implementation, the study explores how institutional HR practices, responsiveness to technological change, and school leadership contribute to enhancing teacher performance. A quantitative correlational approach was applied to test the hypothesis that all three variables positively affect teacher productivity. The findings reveal that the simultaneous F-test result (F = 54.845) exceeds the critical value (2.48) with a significance level of 0.000, indicating a statistically significant influence. Partial T-test results further confirm that each independent variable has a positive effect. The coefficient of determination (R² = 0.674) shows that 67.4% of teacher productivity is explained by the three variables. This study contributes to the development of strategic management practices in education by providing empirical evidence of key factors that enhance teacher productivity. However, the study is limited by its focus on internal school factors, excluding external elements such as policy, community involvement, or student characteristics.